Budaya Organisasi, Kepemimpinan dan Komitmen: Determinan Efektivitas Organisasi yang Akurat - Didit Darmawan (TIN: Terapan Informatika Nusantara, 2022)
In a dynamic and increasingly competitive business world, organizational effectiveness is a major concern for business leaders and practitioners. However, organizational effectiveness is not solely about achieving financial goals, but also involves deeper aspects, including operational efficiency, innovation, adaptation to market changes, and employee engagement. For this reason, this research was conducted to analyze more deeply the problematization of organizational effectiveness by focusing on various factors that influence it, namely organizational culture, leadership, organizational commitment. This research uses a quantitative approach. This research can be started by collecting data through a specially designed employee survey. the research sample is employees who work in one of the multinational companies in the urban area of Surabaya. The identified employees totaled 150 employees. this study used multiple linear regression analysis. The findings of this study reveal that of the three independent variables namely organizational culture, leadership and organizational commitment can affect organizational effectiveness. Organizational culture, leadership and organizational commitment have an important role in shaping the identity and performance of an organization